2006
DOI: 10.1167/iovs.05-1393
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and Biochemical Evaluation of the Porcine Anterior Chamber Perfusion Model

Abstract: These new ultrastructural investigations indicate that the cribriform and subendothelial regions of the porcine TM have an architecture similar to that of the primate TM. The biochemical and physiological response to TGF-beta2 was identical with that described in human TM cell culture and anterior chamber perfusion. The porcine anterior chamber perfusion model is valid for the human system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 20 publications
2
59
0
Order By: Relevance
“…Porcine eyes are a good model for human eyes 28,29 as a model for studying glaucoma, 15,28,30,31 aqueous humor outflow physiology, [31][32][33] and chronic IOP elevation, 28,29 and similar to human, outflow facility in both is reduced in response to TGFb 2 . 32 Porcine TM cells are already widely used by glaucoma researchers as a surrogate for human TM cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Porcine eyes are a good model for human eyes 28,29 as a model for studying glaucoma, 15,28,30,31 aqueous humor outflow physiology, [31][32][33] and chronic IOP elevation, 28,29 and similar to human, outflow facility in both is reduced in response to TGFb 2 . 32 Porcine TM cells are already widely used by glaucoma researchers as a surrogate for human TM cells.…”
Section: Discussionmentioning
confidence: 99%
“…32 Porcine TM cells are already widely used by glaucoma researchers as a surrogate for human TM cells. In this study we employed an established method of isolating AAP cells published by our group previously.…”
Section: Discussionmentioning
confidence: 99%
“…It is found abundantly in TM beams and the JCT region, with slightly higher levels in the basement membranes of TM beam cells, JCT cells and SC inner wall cells (Keller et al, manuscript in review). (Floyd et al 1985;Murphy et al 1987;Zhou et al 1998a;Bachmann et al 2006;Keller et al 2007a) In the JCT at the ultrastructural level, fibronectin is found in the amorphous material associated with the basement membranes and with the peripheral SD material of the elastic microfibrils. (Yue 1996;Brilakis et al 2001;Ueda et al 2002;Ueda and Yue 2003) In addition to forming a thin fibrous array that appears to encircle TM cells in culture, (Zhou et al 1998b) fibronectin also forms thick fibrous strands.…”
Section: Fibronectin and Vitronectinmentioning
confidence: 99%
“…The anterior segment of the porcine eye has an acceptable degree of anatomical and ultrastructural resemblance with the human eye (Bachmann et al 2006), and isolated porcine eyes (WikbergMatsson et al 2000;Wikberg-Matsson & Simonsen 2001) or isolated porcine iris muscles (Toda et al 1999) are established models for investigating ocular adrenoceptors (Toda et al 1999;Wikberg-Matsson et al 2000;Wikberg-Matsson & Simonsen 2001). In addition, for an intracameral mydriatic to be usable in humans safety issues, possible adverse reactions et cetera also have to be addressed.…”
Section: Discussionmentioning
confidence: 99%